Impact of digital marketing on consumer purchasing behavior in Kathmandu Valley - Yadav, Bivek Kumar; Chaturbedi, Dhananjay; Neupane, Pushkar (Nepalese Journal of Management, 2024)
This study examines the impact of digital marketing on consumer buying behavior in Kathmandu Valley. Consumer buying behavior is the dependent variable. The selected independent variables are email marketing, online advertising, social media marketing, video marketing and influencer marketing. The primary source of data is used to assess the opinions of the respondents regarding impact of digital marketing on consumer buying behavior in Kathmandu Valley. The study is based on primary data with 100 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of digital marketing on consumer buying behavior in Kathmandu Valley. The study showed that online advertising has a positive impact on consumer buying behavior. It implies that better online advertising stimulates the buying behavior of the consumer. The result also reveals that social media marketing has a positive impact on consumer buying behavior. It implies that better social media marketing stimulates the buying behavior of the consumer. Moreover, video marketing has a positive impact on consumer buying behavior indicating that better video marketing, stimulates the buying behavior of the consumer. Furthermore, email marketing has a positive impact on consumer buying behavior indicating that better email marketing stimulates the buying behavior of the consumer. Similarly, the result also showed that influencer marketing has a positive impact on consumer buying behavior. It indicates that better marketing through popular influencer stimulate the buying behavior of the consumer.